رعاية الأيتام في ولاية سلانجور : دراسة فقهية تقويمية - Nurul Huda Yaakob (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2013)
An orphan institution plays an important role and contributes towards the betterment of the protection and welfare of orphans. Nonetheless, the absence of guidelines that are applicable to all institutions in Selangor leads to injustice to the welfare of the orphans. The objective of this research is to analyze the management of orphans by focusing on hadhanah (custody), nafqah (maintenance), and tarbiyyah (education) by specific the Shari'ah principle and the practical implementation at Rumah Bakti Dato' Harun in Ulu Klang, and Bait Darul Izzah in Bangi, Selangor. Meanwhile, the compatibility of the practical aspect of protecting orphans with fiqh guidelines is the main concern of this research. This research has been conducted by using two approaches; namely theoretical and analytical approach. Further, the theoretical approach in this research is the collection of the texts regarding the subject and the expressions of the scholars were done whereas analytical methods is analyzing information gathered from interviews with the headmaster and secretary from the both institutions on the management of orphan. The findings disclose the perfectness of protection of orphans in Islam meanwhile in practice the efforts of the institution should be praised, nevertheless the guidelines remain unavailable in managing and protecting orphans in Selangor. Therefore, it is proposed that the government should take an initiative to establish proper guidelines to ensure better protection and welfare of the orphans in Selangor. This research concludes that irrespective of the latest position on the welfare of orphans, there is much more to be done to ensure the interests of the orphans are well taken care of.